ECOLOGICAL GROUND OF SOCIO-ECONOMIC DEVELOPMENT OF RURAL TERRITORIES FOR ACCOUNT OF CREATION OF ECOLOGICAL SETTLEMENTS - Самойлік, М. С. (Scientific Progress & Innovations, 2013)
The ecology and economy estimation of regions of Ukraine is carried out on the basis of model a “natural loss is ecology, social and economy factors” and certain directions of improvement of organizationally-economic structure of ecological settlements in the context of steady development of rural territories. Taking into account, that the standard of living of population in ecological settlements is determined their health level, certainly complex of priority measures on proceeding in the components of quality of natural environment, it is conducted division of regions of Ukraine to direction of improvement of the system of ecologically safe development.